Gambaran kejadian karies dan konsumsi makanan kariogenik pada anak usia 10-12 tahun di Sekolah Dasar Negeri 3 Batur - Intan Pertiwi; Luh Wayan Ayu Rahaswanti; I Wayan Gede Sutadarma (Bali Dental Journal, 2018)
Background: Caries is the main oral disease among Indonesian society. One of the main etiology of the dental caries is cariogenic food intake. Aim: The aim of this study was to investigate the caries incidence and cariogenic food intake pattern among elementary students aged 10 to 12 years old at Batur village, Gianyar, Bali. Methods: This study is a cross sectional descriptive study. The data was collected by filling Food Frequency Questionnaires (FFQ) by 104 elementary students aged 10 to 12 years old to investigate the type and intake pattern of cariogenic food. Results: The result shows that the average of def-t index (decayed, extracted, filled tooth) among respondents was 1,8 (low category), and the average of DMF-T index (Decayed, Missing, Filled Tooth) was 2,78 (moderate category). The highest cariogenic food was candy which was consumed more than 3 times a day and 5 to 6 times a week. Conclusions: The conclusion of the study is that the caries incidence and the cariogenic contained food intake rate are cariogenic contained food intake among elementary student at Batur village, Gianyar, Bali.